2019
DOI: 10.1002/cyto.b.21785
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of CD43, CD81, and CD200 in Classic Versus Variant Hairy Cell Leukemia

Abstract: Background Hairy cell leukemia (HCL) and hairy cell leukemia variant (HCLv) are rare diseases with overlapping clinicopathological features. Features distinguishing HCL from HCLv include expression of CD25, CD123, CD200, annexin‐A1, and the presence of BRAF V600E mutation. HCLv typically lacks these markers, but they may occur in a subgroup of HCL patients with an aggressive clinical course. We examined CD43, CD81, CD79b, and CD200 expression in HCL and HCLv. Methods Multiparametric flow cytometry (FCM) was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 58 publications
0
19
0
2
Order By: Relevance
“…CD81 was considered to function as an oncogene in prostate cancer. Previous studies have revealed differential expression of CD81 in various types of cancers, such as classic vs. variant hairy cell leukemia, breast cancer, and gastric cancer (13,27,28). A study by Vences-Catalan et al indicated that CD81, which is a promoter of tumor growth and metastasis, is widely expressed in most tissues and on the majority of tumor cells (11).…”
Section: Discussionmentioning
confidence: 99%
“…CD81 was considered to function as an oncogene in prostate cancer. Previous studies have revealed differential expression of CD81 in various types of cancers, such as classic vs. variant hairy cell leukemia, breast cancer, and gastric cancer (13,27,28). A study by Vences-Catalan et al indicated that CD81, which is a promoter of tumor growth and metastasis, is widely expressed in most tissues and on the majority of tumor cells (11).…”
Section: Discussionmentioning
confidence: 99%
“…The HCL immunological score is low (0 or 1): there is no expression of CD25 and CD200. CD123 expression is inconstant and weak . Note, SDRPL, also a provisional entity, is different from HCL‐V.…”
Section: How Has the Diagnosis Of Hairy Cell Leukemia And Hcl‐like DImentioning
confidence: 95%
“…Cells are morphologically more difficult to identify but are often characterized by the presence of a prominent nucleolus and display a variant immunophenotype including the absence of CD25 and CD123 . Moreover, CD43, CD81, and CD200 have been reported as able to discriminate both HCL types …”
Section: Cd5‐negative B‐lpdsmentioning
confidence: 99%